Discovery and fine-mapping of kidney function loci in first genome-wide association study in Africans. Issue 16 (30th March 2021) - Fatumo, Segun; Chikowore, Tinashe; Kalyesubula, Robert; Nsubuga, Rebecca N; Asiki, Gershim; Nashiru, Oyekanmi; Seeley, Janet; Crampin, Amelia C; Nitsch, Dorothea; Smeeth, Liam; Kaleebu, Pontiano; Burgess, Stephen; et al.
Abstract: Genome-wide association studies (GWAS) of kidney function have uncovered hundreds of loci, primarily in populations of European ancestry. We have undertaken the first continental African GWAS of estimated glomerular filtration rate (eGFR), a measure of kidney function used to define chronic kidney disease (CKD). We conducted GWAS of eGFR in 3288 East Africans from the Uganda General Population Cohort (GPC) and replicated in 8224 African Americans from the Women's Health Initiative. Loci attaining genome-wide significant evidence for association ( P < 5 × 10 −8 ) were followed up with Bayesian fine-mapping to localize potential causal variants. The predictive power of a genetic risk score (GRS) constructed from previously reported trans-ancestry eGFR lead single nucleotide polymorphism (SNPs) was evaluated in the Uganda GPC. We identified and validated two eGFR loci. At the glycine amidinotransferase ( GATM ) locus, the association signal (lead SNP rs2433603, P = 1.0 × 10 −8 ) in the Uganda GPC GWAS was distinct from previously reported signals at this locus. At the haemoglobin beta ( HBB ) locus, the association signal (lead SNP rs141845179, P = 3.0 × 10 −8 ) has been previously reported. The lead SNP at the HBB locus accounted for 88% of the posterior probability of causality after fine-mapping, but did not colocalise with kidney expression quantitative trait loci. The trans-ancestry GRS of eGFR was not significantly predictive into the Ugandan population. In the first GWAS of eGFR in continental Africa, we validated two previously reported loci at GATM and HBB . At the GATM locus, the association signal was distinct from that previously reported. These results demonstrate the value of performing GWAS in continental Africans, providing a rich genomic resource to larger consortia for further discovery and fine-mapping. The study emphasizes that additional large-scale efforts in Africa are warranted to gain further insight into the genetic architecture of CKD.